Creativity of Islamic Religious Education Teachers in Fostering the Psychomotor Domain of Mentally Disabled Students - Asfiati, Asfiati; Mahdi, Nur Imam; Nasution, Nur Faizah Yazid (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
ABSTRACT. The background to this research problem is that mentally retarded students have intellectual limitations or are often referred to as Down syndrome. So mentally retarded students need help from people in fostering the psychomotor domain. And an effort is needed to overcome the problem through the creativity of Islamic Religious Education teachers in fostering the psychomotor domain of mentally retarded students at the Padangsidimpuan State Special School (SLB), Padangsidimpuan Utara District. The fokus of this research is the creativity of Islamic Religious Education teachers in fostering the psychomotor domain of mentally retarded students. This research methodology is a qualitative approach by describing the phenomena of a situasion that actually accurs in the field. The source of this research is from the results of observations and interviews from parties directly related to this research. The results of the study show the creativity that Islamic Religious Education teachers carry out in fostering the psychomotor domain of mentally retarded students using total communication, presenting visual media or images, and practicing the material being taught, and holding routine religious activities. The inhibiting factors that affect Islamic Religious Education teachers in the teaching and learning process are the difficulty in delivering material, due to limitations of mentally retarded students, delays in students' language development, lack of attention from parents, lack of learning media provided by the school, and minimal government attention to the development of mentally retarded students' education. Keyword: Teacher Creativity, Islamic Religious Education, Psychomotor Domain and Mental Mental Disability.